(untitled) (Green Life Medical College Journal, 2025)
Introduction: Pain is a multifaceted experience, and its management remains a global healthcare challenge. Despite advances, pain is frequently undertreated in emergency, post-operative, and chronic pain settings. Accurate pain assessment and effective management strategies are essential to improve patient outcomes and satisfaction, particularly in resource-limited settings like Bangladesh. So, this article emphasis to throw some lights to evaluate pain reduction and patient satisfaction using validated tools in emergency, post-operative, and chronic pain settings. Methods: A multicenter prospective observational study was conducted between 2016 and 2018 in the Department of Physical Medicine and Rehabilitation, Department of Obstetrics and Gynecology at Bangabandhu Sheikh Mujib Medical University, and Emergency Departments of Shaheed Suhrawardy Medical College Hospital. A total of 300 patients, divided equally among emergency (n=100), post-operative (n=100), and chronic pain (n=100) groups, were selected via random sampling. Pain was assessed using the Visual Analogue Scale (VAS), and patient satisfaction was measured using the MISS-21, APS-POQ-R, and PSRS scales. Data were analyzed using SPSS version 26.0. Results: The mean baseline pain scores for the emergency, post-operative, and chronic pain groups were 7.63, 6.31, and 7.26, respectively. After proper intervention, pain scores were reduced significantly to 4.27, 4.47, and 5.02 (p<0.05 for all). The MISS-21 subscales for the emergency group showed strong satisfaction for distress relief (6.58±0.46) and rapport (6.50±0.41), but discomfort in communication comfort (1.32±0.46). Post-operative satisfaction using APS-POQ-R revealed “good” (54.12±1.43) and “excellent” (49.45±1.86) satisfaction levels. Chronic pain satisfaction assessed with PSRS showed 46% of participants had “good” satisfaction (scores 61–70). Pain intensity showed a moderate negative correlation with PSRS (r=-0.328, p=0.001) but not with MISS-21. Conclusion: Validated tools effectively recorded significant pain reduction and patient satisfaction across emergency, post-operative, and chronic pain settings. Green Life Med. Col. J. 2025; 10(1): 20-25